Recent Developments in Non-thermal Processing Techniques to Improve the Quality and Safety of Milk and Milk Products - Bhujel, Meghna; Rai, Vatsala; Maskey, Bunty (Himalayan Journal of Science and Technology, 2024)
This review has highlighted about the different types of non-thermal processing techniques and their recent development in field of dairy processing. The findings underscore the importance of low temperature processing in nutritional, physical and sensory qualities of dairy products, which have significant implications for new generation market requirement for minimally processed food. Despite the progress made, several gaps may remain, particularly in their feasibility in economical and legal terms including its efficacy to reduce microbial load in comparison to traditional methods of heat treatment. Future research should focus on cost-effective solution for both small and large producers, with minimizing preconceived notion of general consumers about non-thermally processed food and its health effects, which will be crucial for advancing these novel technologies to solve in real world issues for providing minimally processed, fresh like dairy products. Ultimately, the continued exploration in this topic promises to yield valuable result in field of food industries and processing.